Radiation-induced grafting of glycidyl methacrylate onto natural cotton fibers and trimethylamine modification for p-nitrophenol adsorption - Saber, Shihab Ezzuldin M.; Abdullah, Luqman Chuah; Ming Ting, Teo; Md Jamil, Siti Nurul Ain; Choong, Thomas S.Y.; Abdulkareem -Alsultan, G. (Elsevier, 2023)
The pre-irradiation grafting procedure was employed to achieve the grafting of natural cotton fibers (Cot) with glycidyl methacrylate (GMA). It was found that the extent of grafting (DG) of GMA was influenced by the dose of radiation that was absorbed; increased doses led to larger DGs. Dose of 10 kGy was chosen for the preparation of the GMA grafted cotton (Cot-g-GMA); this provided a DG of 200%. Subsequently, (Cot-g-GMA) was modified using Trimethylamine (TMA). In order to describe the physiochemical qualities of the fibrous adsorbent, the fibrous adsorbent was characterized with the use of FTIR, FESEM, XRD, TG-DTG, and pHpzc. In addition, the designed TMA(Cot-g-GMA) adsorbent was utilized to examine the adsorption of p-nitrophenol from aqueous solution. An examination was made of the adsorption kinetics and isotherm in order to permit the elucidation of the adsorption of p-nitrophenol behavior. In accordance with the findings emerging from this work, p-nitrophenol adsorption was described with a pseudo-second order. Moreover, the fact that the Langmuir isotherm model was the best fit was determined by the isotherm analysis. In relation to adsorption capacity, the maximum capacity achieved was 180 mg/g at 298 K. The spontaneous and exothermic nature of adsorption was identified by thermodynamic analysis. Specifically, it is evident that adsorbent can be readily reproduced and recycled with no accompanying loss of adsorptive performance in the alkaline medium. These findings indicate the potential of the fibrous bio adsorbent as a means of eliminating p-nitrophenol from wastewater.